N-α-acetyltransferase 10 protein promotes metastasis by stabilizing matrix metalloproteinase-2 protein in human osteosarcomas. (1st October 2018) - Chien, Ming-Hsien; Lee, Wei-Jiunn; Yang, Yi-Chieh; Tan, Peng; Pan, Ke-Fan; Liu, Yu-Cheng; Tsai, Hsiao-Chi; Hsu, Chun-Hua; Wen, Yu-Ching; Hsiao, Michael; Hua, Kuo-Tai
Abstract: N-α-Acetyltransferase 10 protein (Naa10p) mediates N-terminal acetylation of nascent proteins. Oncogenic or tumor suppressive roles of Naa10p were reported in cancers. Here, we report an oncogenic role of Naa10p in promoting metastasis of osteosarcomas. Higher NAA10 transcripts were observed in metastatic osteosarcoma tissues compared to non-metastatic tissues and were also correlated with a worse prognosis of patients. Knockdown and overexpression of Naa10p in osteosarcoma cells respectively led to decreased and increased cell migratory/invasive abilities. Re-expression of Naa10p, but not an enzymatically inactive mutant, relieved suppression of the invasive ability in vitro and metastasis in vivo imposed by Naa10p-knockdown. According to protease array screening, we identified that matrix metalloproteinase (MMP)-2 was responsible for the Naa10p-induced invasive phenotype. Naa10p was directly associated with MMP-2 protein through its acetyltransferase domain and maintained MMP-2 protein stability via NatA complex activity. MMP-2 expression levels were also significantly correlated with Naa10p levels in osteosarcoma tissues. These results reveal a novel function of Naa10p in the regulation of cell invasiveness by preventing MMP-2 protein degradation that is crucial during osteosarcoma metastasis. Highlights: Naa10p promotes invasion and metastasis of osteosarcoma cells. Naa10p promotes metastasis via increasing MMP-2 expression in osteosarcoma cells. Naa10p acetylates MMP-2 and prevents its degradation via NatA activity.